52.7k views
0 votes
Solve: -1/9 + (-5/9)

2 Answers

2 votes

Answer:

According to the question the answer should be :
(-2)/(3)

Explanation:


-(1)/(9) -(5)/(9)


=(-1)/(9)-(5)/(9)


=(-1)/(9) +(-5)/(9)


=(-2)/(3)

You should be getting the final answer as :
(-2)/(3)

User Haawa
by
5.6k points
3 votes

Answer and Step-by-step explanation:

The solution to this question :
(-2)/(3)

Step 1 : Remove the parentheses :


= -(1)/(9) -(5)/(9)

Step 2 : Since the denominators are equal, combine the fractions :


=(-1-5)/(9)

Step 3 : Subtract the numbers :


-(6)/(9)

Step 4 : Now, cancel the common factor (3) :


=-(2)/(3)

User Hendrik Ebbers
by
4.9k points